A KOREAN PERSPECTIVE ON DEVELOPING A GLOBAL POLICY FOR ADVANCE DIRECTIVES - Kim, Soyoon (Bioethics, 2010)
Despite the wide and daunting array of cross-cultural obstacles that the formulation of a global policy on advance directives will clearly pose, the need is equally evident. Specifically, the expansion of medical services driven by medical tourism, just to name one important example, makes this issue urgently relevant. While ensuring consistency across national borders, a global policy will have the additional and perhaps even more important effect of increasing the use of advance directives in clinical settings and enhancing their effectiveness within each country, regardless of where that country's state of the law currently stands. One cross-cultural issue that may represent a major obstacle in formulating, let alone applying, a global policy is whether patient autonomy as the underlying principle for the use of advance directives is a universal norm or a construct of western traditions that must be reconciled with alternative value systems that may place lesser significance on individual choice. A global policy, at a minimum, must emphasize respect for patient autonomy, provision of medical information, limits to the obligations for physicians, and portability. And though the development of a global policy will be no easy task, active engagement in close collaboration with the World Health Organization can make it possible.